An approach to website design for Turkish universities, based on the emotional responses of students. Issue 1 (1st January 2020) - Abdi, Saed Jama; Greenacre, Zerrin Aşan
Abstract: In this age of advanced technology, every university has a website to endorse their programs and encourage students around the world to join one of their faculties. However, universities give less attention to meet the users' demands for visually attractive websites that satisfy their emotions. This study proposes a Kansei Engineering approach based on human emotion to identify elements of website design that are emotionally appealing to 18–37 year-old students in Turkish universities. A total of 22 Kansei words and 9 sample websites of Turkish universities were selected for the study. The sample consisted of 172 students, who were asked to evaluate the selected websites using Kansei words. A five-point semantic differential scale was used to evaluate the relationship between website elements and the Kansei words. The multivariate statistical methods factor analysis and partial least squares regression were used to implement the Kansei approach. The results displayed that Kansei Engineering methodology and multivariate statistical analyses played a key role in designing an attractive website in order to satisfy student's emotions. It also showed that a pleasant university website should have top menu, small header size, logo on the left side and so on.